2020
DOI: 10.5935/0103-507x.20200044
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of micafungin in patients treated with extracorporeal membrane oxygenation: an observational prospective study

Abstract: Objective To determine micafungin plasma levels and pharmacokinetic behavior in patients treated with extracorporeal membrane oxygenation. Methods The samples were taken through an access point before and after the membrane in two tertiary hospitals in Spain. The times for the calculation of pharmacokinetic curves were before the administration of the drug and 1, 3, 5, 8, 18 and 24 hours after the beginning of the infusion on days one and four. The area under the curve,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In vivo studies found that in infants on ECMO, the Vd of micafungin was 20–90% higher than that reported in infants not on ECMO ( 27 ). However, a prospective observational study carried out in 12 adult patients on ECMO found no significant changes in the pharmacokinetic parameters of micafungin ( 28 ). Infants have less blood volume than adults, so ECMO circuits might have a greater effect on the Vd of micafungin in infants.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo studies found that in infants on ECMO, the Vd of micafungin was 20–90% higher than that reported in infants not on ECMO ( 27 ). However, a prospective observational study carried out in 12 adult patients on ECMO found no significant changes in the pharmacokinetic parameters of micafungin ( 28 ). Infants have less blood volume than adults, so ECMO circuits might have a greater effect on the Vd of micafungin in infants.…”
Section: Discussionmentioning
confidence: 99%
“…While drug loss with micafungin in the ECMO circuit has been reported up to 74%, an observational study found no differences in PK parameters on Days 1 and 4 of treatment in patients on ECMO. 54,55 For treatment of severe infections, higher daily doses of micafungin (150-200 mg every 24 h) have been recommended. 56 Caspofungin is a highly lipophilic antifungal agent with high degree of ECMO circuit sequestration, but no significant PK alterations were reported between patients on ECMO support and matched controls.…”
Section: Sedation and Analgesiamentioning
confidence: 99%
“…Echinocandins are concentration‐dependent agents with both fungicidal and fungistatic activity. While drug loss with micafungin in the ECMO circuit has been reported up to 74%, an observational study found no differences in PK parameters on Days 1 and 4 of treatment in patients on ECMO 54,55 . For treatment of severe infections, higher daily doses of micafungin (150–200 mg every 24 h) have been recommended 56 .…”
Section: Antimicrobialsmentioning
confidence: 99%
“…Lopez-Sanchez et al reported the PK of micafungin in 12 adult patients on ECMO. The PK values on day 1 and day 4 showed no difference between the samples taken before the membrane and those taken after, including C max , C min , V d and CL [ 76 ]. Additionally, there was no significant difference with the AUC in samples taken before and after membrane, and on days 1 and 4.…”
Section: Specific Antifungal Classesmentioning
confidence: 99%